Prospects for adopting system of rice intensification in Sri Lanka: a socioeconomic assessment - Namara, Regassa E.; Weligamage, Parakrama; Barker, Randolph (International Water Management Institute, 2003)
Today, there is an increasing worldwide interest in assessing the potential for maintaining or increasing rice yields by reducing or eliminating the use of chemicals and by decreasing irrigation requirements. The System of Rice Intensification (SRI) first developed in Madagascar and now being tested in many countries, is an example of such an approach. The system is based largely on organic farming principles and additional requirements for spacing and the transplanting of seedlings.